A Review of Modeling Hot Metal Desulfurization. Issue 4 (22nd January 2020) - Visuri, Ville-Valtteri; Vuolio, Tero; Haas, Tim; Fabritius, Timo
Abstract : Hot metal desulfurization serves as the main unit process for removing sulfur in blast‐furnace based steelmaking. The available body of literature on modeling hot metal desulfurization is reviewed to provide an in‐depth analysis of the approaches used and results obtained. The mathematical models for reaction kinetics have evolved from simplistic rate equations to more complex phenomenon‐based models that provide useful information on the effect of physico‐chemical properties and operating parameters on desulfurization efficiency. Data‐driven approaches with varying levels of phenomenological basis have also been proposed with the aim of achieving better predictive performance in industrial scale applications. Bath mixing has been studied using physical and numerical modeling to optimize mixing conditions in ladles and torpedo cars. The coupling of gas‐particle jets and their penetration into the liquid have been a focal point of physical and numerical modeling. In recent years, the fluid flow phenomena in mechanically stirred ladles has been studied extensively using physical and numerical modeling. These studies have focused on the fluid flow field, reagent dispersion, and bubble dispersion. Abstract : In blast‐furnace‐based ironmaking, hot metal desulfurization serves as the main unit process for removing sulfur. It is a complicated metallurgical system, in which thermodynamics, kinetics, and fluid mechanics all play a role. Modeling hot metal desulfurization is reviewed along with an analysis of the approaches used and results obtained.